2021
DOI: 10.1021/acsami.1c03421
|View full text |Cite
|
Sign up to set email alerts
|

Engineered Biomimetic Nanoplatform Protects the Myocardium Against Ischemia/Reperfusion Injury by Inhibiting Pyroptosis

Abstract: Protection of cardiomyocytes against oxidative stress is vital to alleviate myocardial ischemia/reperfusion injury (MI/RI). However, antioxidative treatment is hampered by the lack of safe and effective therapeutics. Polydopamine (PDA), as a biodegradable class of nanomaterial with excellent antioxidant properties, has shown great potential in treating MI/RI. To achieve site-specific antioxidative efficacy, we established a PDA-based biomimetic nanoplatform (PDA@M), which consisted of a polydopamine core and a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
21
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(23 citation statements)
references
References 34 publications
2
21
0
Order By: Relevance
“…[17] Therefore, effectively eliminating excess mitochondrial ROS may be a potential strategy to block NLRP3-mediated pyroptosis for the alleviation of PD. [17,19] Artificial nanozymes have attracted extensive interest in the past decade owing to their prominent advantages, including adjustable catalytic activities, multiple enzyme-like activities, and high stability. [20,21] To date, more than 900 types of nanozymes from different materials have been reported.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[17] Therefore, effectively eliminating excess mitochondrial ROS may be a potential strategy to block NLRP3-mediated pyroptosis for the alleviation of PD. [17,19] Artificial nanozymes have attracted extensive interest in the past decade owing to their prominent advantages, including adjustable catalytic activities, multiple enzyme-like activities, and high stability. [20,21] To date, more than 900 types of nanozymes from different materials have been reported.…”
Section: Introductionmentioning
confidence: 99%
“…[ 17 ] Therefore, effectively eliminating excess mitochondrial ROS may be a potential strategy to block NLRP3‐mediated pyroptosis for the alleviation of PD. [ 17,19 ]…”
Section: Introductionmentioning
confidence: 99%
“…Dopamine is one of the inotropic agents applied clinically to improve cardiac functions in patients suffering from cardiac insufficiency . Studies have reported that dopamine could be assembled into polydopamine, which has been widely used in biomedical fields due to its favorable biocompatibility and biodegradability. Interestingly, due to the presence of phenolic hydroxyl groups, polydopamine exhibits excellent chelating efficiencies against metal ions, including copper, iron, and manganese. , In addition, polydopamine has been identified as an antioxidant that can inhibit inflammation and oxidative stress. , Given the metal ion-chelating, anti-inflammation, and antioxidative stress effects of polydopamine, polydopamine is naturally considered to be an appropriate drug candidate for alleviating myocardial I/R injury and improving cardiac function.…”
Section: Introductionmentioning
confidence: 99%
“…Wei et al reported that a polydopamine-based biomimetic nanoplatform (PDA@M) can inhibit pyroptosis to protect the myocardium against IRI. PDA@M consists of a polydopamine core and a macrophage membrane shell, to achieve site-specific antioxidative efficacy 68 . The results demonstrated that PDA@M targets the infarcted myocardium to suppress the NLRP3/caspase-1 pathway, thus exerting antioxidative and antipyroptosis functions, suggesting that it may serve as a potential therapeutic agent for IRI.…”
Section: Inhibiting Pyroptosis To Treat Inflammatory Diseasesmentioning
confidence: 99%